The influence of thyroid function disorders on pregnant women on the Apgar scale and psychomotor development of the child in the first 18 months of life - Florczyk, Weronika; Weber-Nowakowska, Katarzyna; Gębska, Magdalena (Journal of Education, Health and Sport, 2020)
Introduction. In the prenatal period, there are many exogenous and endogenous factors, which adversely affect the normal development of the fetus and may affect the further development of the child. The impaired reference level of thyroid hormones pregnant woman may entail a number of complications, especially in the first trimester of pregnancy, wherein the process takes place organogenesis and the formation of the nervous system. Goal. The overall objective of the work is to verify the correlation between hypothyroidism and child developmental problems in the first eighteen months of life and the Apgar scale. Materials and methods. The study included 200 pregnant women aged 17 to 40 years of age. The research tool was an online, proprietary questionnaire, which has been placed in social groups, which included pregnant women struggling with hypothyroidism. Conclusions. Developmental disorders up to 18 months of children age occurred in 45% of women with thyroid dysfunction, of which 43% related to symptoms of neurological problems including 56% of impaired muscle tone. The present study demonstrates that the final outcome Apgar does not forecast problems in the course of further development of the child up to 18 months of age. Significant further research, which will help establish the presence of mechanisms adverse impact on offspring and pregnancy outcomes.